Localised pulmonary resection for bronchiectasis in hypogammaglobulinaemic patients. Issue 5 (May 1994) - Cohen, A J; Roifman, C; Brendan, J; Mullen, M; Reid, B; Weisbrod, G; Downey, G P
Abstract : BACKGROUND--Bronchiectasis and pulmonary infections are common in patients with hypogammaglobulinaemia. Despite intravenous gammaglobulin treatment and appropriate antibiotics, a subgroup of patients remains with persistent localised pulmonary infection in segments where bronchiectasis had developed before appropriate treatment. As such localised pulmonary suppuration (segmental or lobar) may serve as a focus for progression of bronchiectasis, surgical resection of the involved segments may be considered. The outcome of pulmonary resection in four such patients is reported. RESULTS--Surgery was well tolerated except for one postoperative empyema. Information on follow up is available from 3.5 to 5 years. All patients experienced considerable reduction of symptoms including cough, sputum production, antibiotic use, and hospital admissions. CONCLUSIONS--Surgical resection of localised bronchiectatic segments should be considered in patients with hypogammaglobulinaemia with persistent localised suppuration and symptoms refractory to medical treatment.